Consumption Uncertainty and Precautionary Saving - Christelis, Dimitris; Georgarakos, Dimitris; Jappelli, Tullio; van Rooij, Maarten (The Review of Economics and Statistics, 2020)
Using survey data from a representative sample of Dutch households, we estimate the strength of precautionary saving by eliciting subjective expectations on future consumption. Expected consumption risk is positively correlated with self-employment and income risk and negatively with age. We insert these subjective expectations (rather than consumption realizations, as in the existing literature) in an Euler equation for consumption and estimate the degree of prudence by associating expected consumption risk with expected consumption growth. Robust OLS and IV estimates indicate a coefficient of relative prudence of around 2. We obtain similar results via partial identification methods using weak assumptions.